Pioneer News - Observer Volume 2 No. 6 (Kerville, TX Pioneer News-Observer, 1971)
This is a full issue of the Pioneer News-Observer for November 1971. The main article is about the daring escape made by the Apache Kid and his group that flee a stagecoach taking them to prison killing the Sheriff and Deputy. There are other articles in this issue talking about Indians and their way of life.
g
Master list item #: 45
File location is in the New Mexico file Cabinet
Keywords: Apache Kid; Apache Indians; Indian Escapes; Pioneer Life and Customs; Indian Life and Customs; News articles